Pelatihan Produksi Arang Menggunakan Kompor Oli Bekas di Desa Pasar Kerkap - zuliantoni, Zulian; Supardi, Nurul Iman; Hardiansyah; FA, A Sofwan (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2025)
This community service activity aims to improve the understanding and skills of school dropouts in Pasar Kerkap Village by providing training in charcoal production using technology derived from used oil stoves. The program is designed using a participatory training approach based on appropriate technology, emphasizing the active role of participants throughout the process. The activity begins with a preparatory phase that includes coordination with village officials, a survey to find participants, the provision of tools and materials, and the development of training modules. Next, a socialization session is held discussing the concepts of renewable energy, biomass waste processing, and how used oil stoves work through interactive lectures and equipment demonstrations. The main part of this activity is hands-on practice in charcoal production, which includes raw material preparation, the charcoal-making process, cooling, packaging, and a simulation of calculating production costs as a form of entrepreneurship education. The mentoring and evaluation phase is carried out to ensure that participants can apply the technology independently, as well as to assess product quality and the sustainability of the program. The results of this activity include the formation of a skilled youth group, environmentally friendly charcoal products with market value, and training modules and videos as learning tools. This program is expected to encourage economic independence and increase environmental awareness by utilizing waste productively.